Synthesis of Cinnamic Acid Based on Perkin Reaction Using Sonochemical Method and Its Potential as Photoprotective Agent - Erwin Indriyanti; Masitoh Suryaning Prahasiwi (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2020)
Cinnamic acid plays a vital role in the synthesis of other important compounds and as a precursor for the synthesis of commercial cinnamon esters used in perfumery, cosmetics, and pharmaceutical industries. The aim of this research is to synthesize cinnamic acid using sonochemical methods. Cinnamic acid was synthesized using Perkin reaction by reacting 0.05 mole of benzaldehyde with 0.073 mole of acetic acid anhydride and 0.03 mole of sodium acetate as a catalyst in the Erlenmeyer flask and then the mixture was put in a sonicator for 60 minutes at 70 oC. The synthesized compound was tested organoleptic properties, and the melting point was measured. The chemical structure was elucidated using FT-IR, H-NMR, and 13C-NMR. The photoprotective activity was examined from its antioxidant and SPF values. The synthesized compound was found in the form of a shiny white fine crystal which had distinctive odor with a yield of 4.98% and the melting point was found at 133 oC. In the structure elucidation using FT-IR (the aromatic ring absorption at the wave number 1580 cm-1 -1600 cm-1. The wave number 1625 cm-1is an aromatic conjugated alkene group, while wave number 1689.4 cm-1 is a carbonyl group. The wave number 2500 cm-1 – 3250 cm-1 is an OH carboxylic acid group) , H-NMR (7.410 (m, 5H, Ar-H); 7.425(t, 1H); 7.572 (d, 1H); 8.057 (d, 1H,C=CH) and 13C-NMR (129.309 ppm; 130.998 ppm; 134.58 ppm; 170.017 ppm) showed that when compared with the standard compound as the reference, the synthesized compound was confirmed to be cinnamic acid. The antioxidant activity test showed that at the concentration of 20 ppm the synthesized compound was able to reduce free radicals by 46.69%. This finding showed that the synthesized compound had antioxidant activity.